What happened in kindergarten? Mother-child conversations about life story chapters. Issue 1 (2nd January 2019) - Leichtman, Michelle D.; Steiner, Kristina L.; Camilleri, Kaitlin A.; Pillemer, David B.; Thomsen, Dorthe Kirkegaard
ABSTRACT: Research indicates that adults form life story chapters, representations of extended time periods that include people, places and activities. Life chapter memories are distinct from episodic memories and have implications for behaviour, self and mental health, yet little is known about their development during childhood. Two exploratory studies examined parent–child conversations about life chapters. In Study 1, mothers recorded naturalistic conversations with their 5–6 year old children about two chapters in the child's life. In Study 2, mothers recorded conversations with their 6–7 year old children about a particular life chapter—the child's kindergarten year—and also about a specific episode of their choice. The results indicated that young children are able to recall and discuss information about life chapters and that parents actively scaffold children's discussion of general information in chapters as well as specific events. Mothers' conversational style when discussing chapters (e.g., elaborativeness) predicted children's memory contributions, and was also positively correlated with their style when discussing specific events. The results suggest new avenues for research on the ontogeny of life chapters, the factors that shape them, and their role in development.